Utilization of Virtual Assistance (Chatbot) for an Integrated Information Portal as Part of a Marine Tourism Promotion Strategy in Banten. - Hamdan, Hamdan; Romli, Ombi; Auliana, Sigit; Permana, Basuki Rakhim Setya (JINAV: Journal of Information and Visualization, 2024)
This study aims to develop and analyze the implementation of Virtual Assistance (Chatbot) as an integrated information medium for marine tourism promotion in Banten Province. The chatbot technology is designed to provide easy access to real-time information about tourist destinations for prospective visitors. The research was conducted at several popular beaches in Banten, such as Carita, Anyer, Sawarna, and Tanjung Lesung. Through surveys of visitors and tourism operators, data on the effectiveness of chatbots were collected and analyzed. The results show that the implementation of chatbots helps improve tourist satisfaction in information-seeking and strengthens the promotion of marine tourism in Banten.